ASSESSMENT AND DISCLOSURE OF INFORMATION IN THE FINANCIAL REPORTING OF INVESTMENT PROPERTY - Z.M. Shaukerova,; D.M. Aykupesheva, (Academic Journal of Physical and Chemical Sciences, 2019)
At the present stage, the activities of organizations for the acquisition or creation of real estate objects with a view to their subsequent transfer to operating leases has become widespread. So the real estate market has become an attractive segment of business entities for investing free own funds. According to the authors, many enterprises seek to keep buildings and structures on the balance sheet, or land not used in the main activity of the company, that is, they seek to lease them. Companies can also invest in land or premises. With favorable market conditions, their value will increase, which will increase the capitalization of the business. Such assets are reflected in the balance sheet in accordance with IFRS as investment property and are accounted for separately from the company's fixed assets.